The impact of knowledge management capability and intellectual capital on business performance in the mediation of innovation capability - Huynh, Tam Minh; Nguyen, Ha Hong; Nguyen, Ky (Edelweiss Applied Science and Technology, 2024)
The objective of this study was to examine the relationship between knowledge management capability, intellectual capital and business performance through the role of innovation capabilities in tourism companies in Ho Chi Minh City, Vietnam. Especially this study bricks of building determinants of business performance as well as knowledge management capability and intellectual capital for future consideration. The study was conducted by surveying 415 managers who are members of the Board of Directors who directly run tourism companies in Ho Chi Minh City and data was collected from October 2022 to May 2023. Inheriting the researches by Waseem Barkat, Riaz Ahmed, Loo-See Beh & Adeel Ahmed (2018); Ali Junaid Khan, Muhammad Sajid Tufail, Asad Ali (2021); & Aboobucker Ilmudeen, Yukun Bao, Ibraheem Mubarak Alharbi & Zubair Nawaz (2021), the authors used confirmatory factor analysis (CFA) to determine the most common observed variables of each factor. Research findings indicated that knowledge management capability, intellectual capital and innovation capability impacted business performance and confirmed the mediating role of innovation capability towards previous variables by the SEM model. From the above results, the study has suggested managerial implications to further improve the investment in developing knowledge management capability, intellectual capital elements and innovation capacity to achieve high business results in tourism enterprises in Ho Chi Minh City, Vietnam in the future.